Pengaruh Motivasi Kerja dan Kompensasi Terhadap Kinerja Karyawan Apotek di Wilayah Kec. Ciawigebang Kab. Kuningan - Nuri Nur’aeni; Nelly Martini (Journal of Management and Creative Business, 2026)
Fierce business competition demands effective human resource management to maintain employee performance as a strategic asset of the organization. This study aims to provide an empirical overview of the influence of work motivation and compensation on the performance of pharmacy employees in the Ciawigebang subdistrict, Kuningan Regency. The research method used was a descriptive quantitative approach. Data were collected through questionnaires and document analysis, then analyzed using SPSS 26. This study involved 50 respondents from 8 pharmacies in Ciawigebang Subdistrict, Kuningan Regency, which served as both the population and the sample. The findings indicate that the variables under study are valid and reliable. Work motivation has a positive and significant partial effect on employee performance. Compensation also has a positive and significant partial effect. Simultaneously, work motivation and compensation have a significant effect on employee performance, contributing 19.5% of the total effect, while the remaining 80.5% is influenced by other factors outside the scope of this study. The conclusions and contributions of this study reveal that although the compensation received by employees is below the Kuningan Regency Minimum Wage (UMK), employees still consider it fair because it is commensurate with their workload, thus not adversely affecting the quality of their performance. It is hoped that the results of this study will help pharmacy managers implement more effective human resource management.